Aspect of Mobbing Behaviors Incurred on the Staff Working at the Directorates of Youth Centers - Hacıcaferoğlu, Serkan (Journal of Sports Research, 2015)
This study was carried out having the purpose of determining the aspect of the mobbing behaviors incurred on the staff working at the youth center directorates of the in Turkey Youth Services and Sports, the Province Directorates. The sample of the study, which was conducted by using a scanning model, was consisted of 253 employees working at the directorate of the youth centers in different regions, who were selected by a random method. The study data were collected by the "Negative Behaviors Questionnaire (NAQ)”. Arithmetic mean, crosstab, t-test, one-way analysis of variance and Tukey’s test were used in the survey. As the result of the survey, it was found out that 44.7% of the staff in the sample was exposed to mobbing behaviors at a lower medium level during the past six months. Additionally, it was also identified that the contractual civil servants of the staff were exposed to mobbing behaviors at a total ratio of 57.5%. It has been identified that the mobbing actions have been incurred downward upon the contractual civil servants by the branch managers (21.5%) and the managers of the youth centers (18.5%), upon the permanent staff by the branch managers (42.9%), and upon the managers of the youth centers by the provincial directors (66.7%).